Graphene oxide accelerates diabetic wound repair by inhibiting apoptosis of Ad‐MSCs via Linc00324/miR‐7977/STK4 pathway. Issue 11 (21st October 2022) - Ji, Zhe; Wang, Jian; Yang, Shuai; Tao, Shengjun; Shen, Caiqi; Wei, Hanxiao; Li, Qiang; Jin, Peisheng
Abstract: Many studies have shown that graphene oxide (GO) promotes proliferation and differentiation of a variety of stem cells. However, its effect on adipose‐derived mesenchymal stem cell (Ad‐MSCs) apoptosis is still unclear. Apoptosis is a significant factor affecting stem cell‐based treatment of diabetic wounds. Therefore, we explored the effect of GO on Ad‐MSC apoptosis and diabetic wound healing. In this study, qRT‐PCR was used to detect Ad‐MSC expression of LncRNAs, miRNAs, and mRNAs under high‐glucose environment. RNA immunoprecipitation (RIP), RNA pull‐down, and luciferase assays were used to detect interactions of specific lncRNAs, miRNAs, and mRNAs. The effects of GO on Ad‐MSC apoptosis were explored by flow cytometry, TUNEL assay, and Western blot. A diabetic wound model was used to explore the function of Linc00324 on Ad‐MSC reparative properties in vivo. As a result, GO inhibited high glucose‐induced apoptosis in Ad‐MSCs, and Linc00324 contributed to the anti‐apoptotic effect of GO. RIP and RNA pull‐down confirmed that Linc00324 directly interacted with miR‐7977, functioning as a miRNA sponge to regulate expression of the miR‐7977 target gene STK4 (MST1) and downstream signaling pathways. In addition, GO reduced the apoptosis of Ad‐MSCs in wounds and promoted wound healing. Taken together, these findings suggest GO may be a superior auxiliary material for Ad‐MSCs to facilitate diabetic wound healing via the Linc00324/miR‐7977/STK4 pathway.